Factors of Acceptance of Mobile Banking in Malaysia - Bakri, M. H. (International Journal of Human and Technology Interaction (IJHaTI), 2020)
As of now in the advanced world, mobile application and web-based computerized are quickly evolving. One of developing financial innovation is financial technology, especially in mobile banking. One emerging financial innovation is mobile banking service. The mobile banking services of Malaysia are now very much concerned with the importance of client perception and acceptance. This research aimed to study the determinants of customer acceptance towards using mobile banking services in Malaysia. There are five research objectives identified which were to analyzetheinfluenceofperceivedusefulness,to examine the influence of perceived ease of use, to determine the influence of perceived cost and to identify the influence of security on customer acceptance towards using mobile banking service in Malaysia. To study the determinants of customer acceptance towards using mobile banking service, the researcher selects the 384 customers as our sample framework. The researcher used correlation analysis and multiple regression analysis to analyses the data. The results depict that there is a significant relationship between perceived usefulness, perceived ease of use, security and perceived cost (independent variable) and the Customer Acceptance (dependent variable). The researcher recommended that future research could cover other areas in Malaysia and cover more specific customer acceptance and perception in mobile banking to provide more useful and accurate data for financial industries. Keywords—mobile banking; acceptance; ease of use; cost; usefulness